Ideal workers and ideal parents: Working-time norms and the acceptance of part-time and parental leave at the workplace in Germany - Yvonne Lott; Christina Klenner (Hans-Böckler-Stiftung, Wirtschafts- und Sozialwissenschaftliches Institut (WSI), 2016)
This study examines the extent to which the use of part-time work and parental leave is accepted in German workplaces for women and men as well as various work positions and professions. Interviews were conducted with 95 employees and 26 experts in hospitals, police stations and industrial companies. The results indicate that the working-time norms not only vary according to gender, but to the position in the workplace hierarchy and profession. Moreover, working-time norms are shifting. Part-time work and parental leave is gradually more accepted in higher status position and for men. In addition to the norms, other factors - especially staffing issues and the behavior of management personnel - are decisive for acceptance, and thus for the work behavior of employees.
Keywords: 330